Ενεργειακή απόδοση και συμπεριφορά οικιστικών μονάδων στην Κύπρο - Ιωάννου, Ανδρέας (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2013)
The purpose of the current project is the calculation and analysis of energy consumption of residential dwellings in Cyprus. The whole analysis is based on the processing of data which were taken from sensors positioned in selected homes in the whole of Cyprus. The above data processing has produced detailed observations concerning the storage of solar energy, energy consumption for heating purposes as well as other energy factors. Specifically, separate calculations have been produced which take into account the amount of energy stored in each wall in every house under study. In the first chapter, separate references are made to scientific research which was conducted on the same subject matter. As this is a pilot research there are no corresponding articles, however, there are studies which use other methodologies to calculate energy consumption in similar cases. In the second chapter, the basic underlying scientific theory is presented, which must be taken into account, for a full comprehension of the principles which govern this pilot project, while at the third chapter, the aims of the research project have been analysed and information concerning the relevant qualifications and responsibilities of each participant is given. In addition, references are made to the importance of the project as no similar work has been carried out on the island in the past. Similar projects which have been carried out in other countries in the past cannot be used as reference case-studies because of the wide environmental differences as well as the differences in the construction materials. In the fourth chapter, the methodology which was followed for the calculation and study of the energy consumption and the calculations of wall and roof temperature conductivity in each house under study has also been given. Furthermore, presentations illustrate the amount of energy load saved due to the impact of solar radiation, the total input of energy each month due solar radiation in kJ/m2, as well as calculations which show the total thermal loss in each house during each 24 hour day for each month (kJ/m2). In addition the calculation showing the gain in terms of thermal load from each wall and each roof for each day of February is presented. A presentation using graphics verifies the results for each wall and rooftop. The square metres of the walls of houses A, B and C have been calculated using architectural plans. In addition the density (kg/m3) and special thermal conductivity (kJ/kgK) of the structural materials have been calculated in order to estimate the amount of energy stored in each house. Next, the amount of energy stored in each wall facing East, North, South, West and the roof top of each house has been calculated separately in addition to the total energy stored in each house.
Keywords: Sensors; Energy Consumption; Aισθητήρες; Eνεργειακή Kατανάλωση